Early life microbiome perturbation alters pulmonary responses to ozone in male mice. Issue 2 (24th January 2020) - Brown, Traci A.; Tashiro, Hiroki; Kasahara, David I.; Cho, Youngji; Shore, Stephanie A.
Abstract: Early life changes in the microbiome contribute to the development of allergic asthma, but little is known about the importance of the microbiome for other forms of asthma. Ozone is a nonatopic asthma trigger that causes airway hyperresponsiveness and neutrophil recruitment to the lungs. The purpose of this study was to test the hypothesis that early life perturbations in the gut microbiome influence subsequent responses to ozone. To that end, we placed weanling mouse pups from The Jackson Laboratories or from Taconic Farms in sex‐specific cages either with other mice from the same vendor (same‐housed) or with mice from the opposite vendor (cohoused). Mice were maintained with these cagemates until use. The gut microbial community differs in mice from Jackson Labs and Taconic Farms, and cohousing mice transfers fecal microbiota from one mouse to another. Indeed, 16S rRNA sequencing of fecal DNA indicated that differences in the gut microbiomes of Jackson and Taconic same‐housed mice were largely abolished when the mice were cohoused. At 10–12 weeks of age, mice were exposed to room air or ozone (2 ppm for 3 hr). Compared to same‐housed mice, cohoused male but not female mice had reduced ozone‐induced airway hyperresponsiveness and reduced ozone‐induced increases in bronchoalveolar lavage neutrophils. Ozone‐induced airway hyperresponsiveness was greater in male than in female mice and the sex difference was largely abolished in cohoused mice. The data indicate a role for early life microbial perturbations in pulmonary responses to a nonallergic asthma trigger. Abstract : We altered the gut microbiomes of weanling mice by placing them in cages occupied by mice from another vendor. Our data indicate that in male mice, early life microbial perturbations alter the pulmonary response to ozone.